A case study: Identification of the existence of Dyslexics among pupils in a school in Sarawak / Siti Huzaimah Sahari - Sahari, Siti Huzaimah (2007)
Dyslexia is a type of learning difficulties suffered by millions of people in this world. Studies on dyslexia are still considered new in Malaysia and not many reports and studies recorded. This case study aims to find out the existence of dyslexia among primary school pupils. A number of 20 pupils from SK St Anne, Sarikei, Sarawak, who are identified as low achievers and have reading problems by their teachers is used. Questionnaires are the research instruments, which were answered by the pupils individually and also the teachers through their observation. The questionnaires are constructed based on Ronald Davis (1992) list of Dyslexia symptoms. The symptoms are categorized into 6 categories: general features of dyslexia, reading and spelling, vision and speech, writing and motor skills, mathematics and time management, and personality. The finding is all 20 pupils fit the description of dyslexia. This means they display or experience more than 10 symptoms of dyslexia. 40% of the pupils displays 11 to 17 symptoms, 25% shows between 19 to 13 symptoms and 35% depicts 24 to 19 symptoms. This result explains the existence of dyslexics among underachiever pupils with reading difficulties. With this knowledge, we can help these pupils with learning difficulties as dyslexia is a curable defect. The help can be derived from government, Ministry of Education, teachers in preschools and primary schools, parents and the society in general. Enormous number of dyslexics have overcome their problems and become successful and famous in their life.